ONLINE DISPUTE RESOLUTION AS A SOLUTION TO E-COMMERCE DISPUTES: A COMPARATIVE STUDY OF PAKISTAN AND UK - Akhtar, Dr. Naureen; Khan, Aamir; Imran Habib, Dr. Rao; Rehman Saleem, Hafiz Abdul (The journal of contemporary issues in business and government, 2022)
The primary aim of this paper is to analyze the online dispute resolution (ODR) as a solution to E-commerce disputes. E-commerce is growing increasingly all over the world. The gradual development of this industry has also brought the issue of E-commerce disputes. The nature of disputes makes it difficult for parties to resolve it through conventional platforms such as courts and alternative dispute resolution (ADR). Therefore, ODR mechanism presents more viable solution for the E-consumers. However, in Pakistan, the regulatory and technological development of ODR is still ve/ y insufficient as the E-commerce is an infant industry but with solid growth rate. Therefore, this paper fills this gap and examines the regulatory and technological framework of ODR via comparative study in Pakistan and UK. For this research work, the comparative research approach has been utilized that is based on documentary analysis. It conducts a comparative study of ODR as solution to E-commerce disputes in Pakistan and UK. This paper analytically studies the parliamentaiy statutes and regulations in Pakistan, UK and international laws and other existing data and studies relating to ODR as solution to E-commerce disputes. At this moment, it's questionable if Pakistan's attempt to dealing with it is genuine and whether the existing inadequate ODR legislation can address the challenges. This research finds that, in order to safeguard online consumers, Pakistan is in a dire need to establish a legal framework for online dispute resolution. The lack of defined legislative criteria for ODR services causes several challenges, especially when public compliance is required. Furthermore, this research finds that the introduction of a mandatory automated negations, online mediation, and e-courts, as first step, might be helpful in this regard as the nature of e-disputes requires quick decisionmaking due to its economic nature in order to avoid further loss. Moreover, this study concludes that the confidence of e-consumer can be increased if they are provided with an effective mechanism for redressal of their grievances.